Silver Nanoparticles 2010
DOI: 10.5772/8506
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles in Oxide Glasses: Technologies and Properties

Abstract: Intr"ducti"nNano-size particles of noble metals (Ag, Au, Pt) are today a subject of thorough attention of scientific researchers and of technologists, because these particles reveal the wide range of physical features, absent in the case of bulk media. Size-controlled optical properties of Ag-nanoparticles open good prospects for potential technological applications -such as diffraction elements, optical filters, nanoplasmonic devices, bi-sensors, and nonlinear media. Silver nanoparticles can be produced in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(21 reference statements)
0
10
0
1
Order By: Relevance
“…Small aggregates (such as Ag-pairs, trimers) can be understood as intermediate species before the precipitation of metallic NPs. Their presence suggests that post-exchange annealing led to increase the size of the molecule of nucleus Ag 0 into silver NPs Ag n as follows: Ag 0 → Ag 2 + → Ag 3 + /Ag 3 2+ → ⋯ → Ag n [39]. The observed PL behavior can be related to a progressive Ag aggregation as it was observed in [35,40].…”
Section: Characterization Of Samplesmentioning
confidence: 61%
“…Small aggregates (such as Ag-pairs, trimers) can be understood as intermediate species before the precipitation of metallic NPs. Their presence suggests that post-exchange annealing led to increase the size of the molecule of nucleus Ag 0 into silver NPs Ag n as follows: Ag 0 → Ag 2 + → Ag 3 + /Ag 3 2+ → ⋯ → Ag n [39]. The observed PL behavior can be related to a progressive Ag aggregation as it was observed in [35,40].…”
Section: Characterization Of Samplesmentioning
confidence: 61%
“…Vostokov et al [32] reported the capability of the electron beam irradiation in the formation of 2D metallic nanostructures in Ag and Cu-doped glasses. Studies on the formation of silver nanoparticles of various diameters in glasses under low-energy electron beam irradiation have been reported by Nikonorov et al [14,[32][33][34][35] and Brunov and co-workers [36]. These studies concentrate on general charge-induced surface aggregation observed ex situ by light microscopy without nanoscale imaging of the actual particle-enriched glass surface.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been used to prepare nanoparticles in oxide glasses, ranging from the standard annealing processes, or sol-gel preparation, over ion-exchange by diffusion, ion implantation, to irradiation with photon or particle beams [13][14][15][16][17][18][19][20][21][22]. Amongst the latter, laser irradiation [23,24] is the most established technique in particular for the precipitation of copper and silver nanoparticles in glass.…”
Section: Introductionmentioning
confidence: 99%
“…The shift of the maximum of the plasmon absorption band to λ 420 nm indicates that the silver nanoparticle is surrounded by a dielectric shell with n ≈ 1.5 (see, for example, Ref. 25).…”
Section: Resultsmentioning
confidence: 99%